PERAN INTRAOPERATIF NEUROFISIOLOGI MONITORING DALAM PENATALAKSANAAN PENYAKIT PEREDARAN DARAH OTAK - Sendjaja Muljadi*, Jusuf Misbach** (NEURONA, 2009)
THE INTRAOPERATIVE NEUROPHYSIOLOGY MONITORING IS A NEW PART OF NEUROPHYSIOLOGY DEPARTMENT THE DEVICES IS USED TO ASSIST THE OPERATIONS WHICH DONE BY THE SURGERIES WHERE THE OPERATION FIELD FULL OF THE NERVES TISSUES PARTICULARLY NEUROSURGEON ALSO COULD ASSIST THE ENT DOCTORS OR ORTHOPAEDIC DOCTORS